Disparity in rates of HPV infection and cervical cancer in underserved US populations - Karuri, Asok Ranjan (Front Biosci (Schol Ed), 2017)
There is a higher rate of HPV infection and cervical cancer incidence and mortality in underserved US population who reside in Appalachian mountain region compared to Northern Plains. Social and behavioral factors such as smoking and alcohol consumption are for such a high incidence. However, by and large, the reasons for these discrepancies lie in the reluctance of the underserved population to adopt preventive measures such as prophylactic Human papilloma virus (HPV) vaccines and Pap smear screening that have significantly reduced the incidence and mortality rate of cervical cancer in Caucasian women. Thus, it is clear that drastic change in social behavior and implementation of preventive measures is required to effectively reduce the incidence and mortality from cervical cancer in this underserved population.